From Regulation to Implementation: Challenges in the European Data Economy - Čelik, Nejc; Pesek, Matevž; Žnideršič, Klara; Juvan, Jure; Blatnik, Staša; Lenart, Gregor; Kljajić Borštnar, Mirjana (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Over the past two decades, open data sharing, reuse and data-driven innovation have become essential components of the digital economy in Slovenia and across Europe. The European Strategy for Data and the Data Act aim to create a single data market and promote common European data spaces that support data accessibility, interoperability, and sovereignty. Despite regulatory progress, challenges remain in terms of companies' ability to implement data sharing regulations, integrate into data ecosystems, and develop sustainable business models. For this purpose, we conducted a systematic literature review to identify research gaps in the field of data economy integration, using the PRISMA model. Preliminary findings indicate a lack of practical implementations and maturity of data spaces, highlighting the need for further research on regulatory compliance, technology readiness and value creation strategies. The findings contribute to a deeper understanding of how enterprises can effectively navigate the evolving data economy and leverage data sharing frameworks for innovation and growth.